2018
DOI: 10.2175/106143017x15131012153185
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment for Indirect Potable Reuse: A Case Study from Reno, Nevada

Abstract: A triple bottom line (TBL) approach was used to examine the trade-offs between potential reclaimed water management strategies in a closed basin. The goals of the water management strategy included minimizing water source shortages, ensuring safe and resilient future water supplies, and protecting inland ecosystems through adequate surface flows. The TBL approach consisted of quantitative and qualitative impact assessments of social, environmental, and economic criteria. This research examined how potable reus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This trend showcases the critical need for implementing strategies such as potable reuse, which can address both water supply availability and winter effluent management, a critical issue in the greater Reno area. A triple bottom line (TBL) analysis of Reno's water management alternatives conducted revealed potable reuse of municipal wastewater effluent as one of the key strategies for maintaining long‐term water sustainability (Haak et al, ). Groundwater augmentation can be achieved via (a) surface spreading, and (b) injection wells.…”
Section: Introductionmentioning
confidence: 99%
“…This trend showcases the critical need for implementing strategies such as potable reuse, which can address both water supply availability and winter effluent management, a critical issue in the greater Reno area. A triple bottom line (TBL) analysis of Reno's water management alternatives conducted revealed potable reuse of municipal wastewater effluent as one of the key strategies for maintaining long‐term water sustainability (Haak et al, ). Groundwater augmentation can be achieved via (a) surface spreading, and (b) injection wells.…”
Section: Introductionmentioning
confidence: 99%
“…When considering various water supply alternatives, the evaluation and optimization of life cycle cost can be invaluable to the decision‐making process (Bradshaw, Ashoori, Osorio, & Luthy, ). A more comprehensive triple bottom line analysis might even be warranted because of its ability to simultaneously consider the social, environmental, and economic implications of an engineering design (Haak, Sundaram, & Pagilla, ; Schimmoller, Kealy, & Foster, ; Schoen et al, ). With respect to social considerations, the recent literature demonstrates that, when designed and operated properly, potable reuse systems provide adequate protection of public health (Amoueyan, Ahmad, Eisenberg, & Gerrity, ; Amoueyan, Ahmad, Eisenberg, Pecson, & Gerrity, ; Chaudhry, Hamilton, Haas, & Nelson, ; Pecson et al, ; Pecson, Trussell, Pisarenko, & Trussell, ; Soller, Eftim, Warren, & Nappier, ).…”
Section: Introductionmentioning
confidence: 99%
“…Local agencies and water providers are interested in exploring ways to reduce the cost of water in order to maintain low water rates for users. In several areas of northern Nevada, water is increasingly expensive due to the need to import water supplies from other basins or to acquire additional water rights to provide sufficient water supply to residents [32]. As the northern Nevada urban population grows, local agencies view potable reuse as a means to simultaneously augment water supplies while minimizing wastewater disposal.…”
Section: Potential For Ipr In Reno-sparks Nevada Usamentioning
confidence: 99%
“…It is unknown, though, to what extent residents in northern Nevada are aware of, or have heard of, reclaimed water use, which studies have found to be a significant predictor of public acceptance of reclaimed water's integration into regional water supplies [14]. Reclaimed water use in Reno-Sparks is currently limited to non-potable purposes, however regional partners are exploring the feasibility of indirect potable reuse (IPR) to serve areas in and around the metropolitan area of the Reno-Sparks [32]. The public's perceptions and willingness to consider a greater integration of reclaimed water in its water supply in the Reno-Sparks region is currently unknown.…”
Section: Introductionmentioning
confidence: 99%